Pemanfaatan Minyak Sereh Sebagai Biolarvasida dan Repellent untuk Pencegahan Penyebaran Malaria pada Masyarakat di Kelurahan Dobonsolo Kabupaten Jayapura - Dzukharian Munandar; Rahayu Samalo; Adrian L. Tumeno (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Malaria remains a major public health challenge in endemic areas such as Jayapura District. Strengthening the capacity of health cadres through education and practical training is a strategic step in malaria prevention efforts. This community service activity aimed to improve the knowledge and skills of malaria cadres through health education and demonstration of how to prepare biolarvicide and repellent formulations using lemongrass oil (Cymbopogon citratus). The methods used included a pre-test, educational sessions, practical training, post-test, and skills evaluation. The results showed a significant increase in knowledge, with an average pre-test score of 77.39 and a post-test score of 97.39. All participants showed improvement in their scores, with the majority achieving the maximum score in the post-test. Additionally, participants demonstrated good to excellent practical skills in preparing the formulations, as observed directly. These findings indicate that an educational and hands-on approach in community engagement activities is effective in enhancing the capacity of malaria cadres in the Khomba Waliyauw Community Health Center area.